ผลของกรรมวิธีละลายต่อโครงสร้างจุลภาคของโลหะผสมพิเศษ GTD-111 - ปิยภัทร วงศ์นวปรีชาชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The general standard reheat treatment condition to refurbishment long-term serviced turbine blades, which are made of cast nickel based superalloy, GTD-111, is usually following by solution treatment at 1438 K, 1458 K and 1478 K for 10.8 to 14.4 ks, combination with primary aging at 1328 K for 3.6 ks, and secondary aging at 1118 K for 86.4 ks. However, in practical reheat treatment process, the change of temperature during any heat treating could occur accidentally any time. To simulate this effect, the droppings of temperatures during solution treatment were chosen and carried out to temperature level of 1118 K then heating again to the solution temperature levels. The temperature droppings (according to various simulated programs) were performed during solution treatment. From the results, it was found that effect of temperature dropping during solution treatment greatly influenced the final rejuvenated microstructures.